(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study explores various strategies to achieve this goal, focusing on simplifying tax processes, improving communication, and leveraging technology. Simplifying tax forms and filing procedures can reduce complexity and make compliance more accessible. Streamlining these processes involves creating user-friendly digital interfaces and minimizing bureaucratic hurdles, thereby easing the burden on taxpayers and reducing errors. Improving communication is another critical strategy. Clear, accurate, and timely information about tax obligations and changes in regulations helps taxpayers understand their responsibilities and deadlines. Employing multiple communication channels, including digital platforms and traditional methods, ensures that information reaches a diverse audience effectively. The integration of advanced technology plays a significant role in enhancing taxpayer services. Developing robust online platforms, offering digital payment options, and providing real-time support through virtual assistants can greatly facilitate tax compliance. Additionally, leveraging data analytics allows for targeted outreach and personalized support, addressing common pain points and improving overall service delivery. Personalized support and streamlined dispute resolution processes are also essential. Tailoring services to individual needs and ensuring a transparent, efficient resolution process for disputes help build trust and encourage timely compliance. Building partnerships with professional organizations, community groups, and businesses can extend the reach of tax services and provide additional support. Moreover, enhancing data security is crucial for protecting taxpayer information and maintaining confidence in the system. Soliciting regular feedback from taxpayers enables continuous improvement and adaptation of services. By implementing these strategies, tax authorities can foster a more supportive and efficient tax environment, leading to higher compliance rates and better public service outcomes.